Squamocin Suppresses Tumor Growth through Triggering an Endoplasmic Reticulum Stress‐Associated Degradation of EZH2/MYC Axis - Yin Zhu; Yurui Liu; Xiangtao Wang; Zhifeng Chen; Baojian Chen; Bingxin Hu; Tiane Tang; Haoran Cheng; Xinglong Liu; Yunshan Ning (Advanced Science)
Abstract Despite substantial advances in the antitumor effects of annonaceous acetogenins (ACGs), the absence of a defined biological action mechanism remains a major barrier to their clinical application. Here, it is found that squamocin effectively depletes both EZH2 and MYC in multiple cancer cell lines, including head and neck squamous cell carcinoma, and gastric and colorectal cancer, demonstrating potent efficacy in suppressing these in vivo tumor models. Through the combination of surface plasmon resonance (SPR), differential scanning fluorimetry (DSF), and cellular thermal shift assay (CETSA), heat shock protein 90α (HSP90α) is identified as the direct binding target of squamocin. Mechanistically, squamocin disrupts mitochondrial respiratory Complex I function, reduces ATP production, and impairs HSP90α function, provoking endoplasmic reticulum (ER) stress and the unfolded protein response (UPR). These intrinsic events within tumor cells enhance ER stress‐associated ubiquitylation and degradation by triggering ubiquitin via the E1 activase UBA6, facilitating ubiquitin transferring to E2 conjugate UBE2Z and increasing the activities of E3 ligase FBXW7 to degrade both EZH2 and MYC. The findings elucidate the role of squamocin in the degradation of oncoproteins EZH2 and MYC by triggering an ER stress‐associated UBA6‐UBE2Z‐FBXW7 ubiquitin cascade, providing insights that may accelerate therapeutic development targeting tumors driven by the EZH2/MYC axis.